Wheat crop in the state of Rio Grande do Sul, Brazil, 2018. - CASTRO, R. L. de (2020)
Rio Grande do Sul is one of the main wheat-producing states in Brazil. Our objective was to analyze the wheat crop in RS in 2018. In 2018, RS harvested 709,558 ha of wheat (34.2% of the total area harvested in Brazil), producing 1,750,700 tons of wheat (32.3% of the Brazilian production), with an average of grain yield of 2,467 kg/ha (157 kg/ha below the Brazilian average of 2,624 kg/ha).